Patients' demographic and socioeconomic characteristics influence the therapeutic decision-making process in psoriasis. - Emanuele Scala; Matteo Megna; Paolo Amerio; Giuseppe Argenziano; Graziella Babino; Federico Bardazzi; Luca Bianchi; Giacomo Caldarola; Anna Campanati; Serafinella Patrizia Cannavò; Andrea Chiricozzi; Andrea Conti; et al. (PLoS ONE, 2020)
BACKGROUND:Knowledge regarding differences in care for psoriatic patients is limited. The aim of this study was to investigate factors influencing prescription of systemic treatments for patients with psoriasis with a special focus on socioeconomic factors. METHODS AND FINDINGS:This was a non-interventional, cross-sectional study, conducted in 18 Italian University and/or hospital centers with psoriasis-specialized units. Questionnaires evaluating demographic and socioeconomic characteristics were administered to participants. Overall, 1880 consecutive patients affected by mild-to-severe psoriasis were recruited. Univariate and multivariable logistic regression analyses of systemic therapy prescription, with a special focus on biologics, accounting for the above mentioned characteristics were performed. Our analysis showed that all analyzed patients' characteristics were significantly associated with biological therapy compared to non-biological systemic one. Particularly, women were less likely to receive biologics than men (OR = 0.66; 95% CI, 0.57-0.77). Elderly patients (≥65 years) and subjects with a BMI ≥30 had lower odds to receive biologics respect to adults (≥35-64 years) (OR = 0.33; 95% CI, 0.25-0.40), and subjects with BMI≥25<30 (OR = 0.64; 95% CI, 0.53-0.77), respectively. Northern and Southern patients were both less likely to receive biologics than Central patients (OR = 0.75; 95% CI, 0.63-0.89, and OR = 0.56; 95% CI,0.47-0.68, respectively). Lower economic profile and never reading books were both associated with decreased odds of receiving biological therapy. CONCLUSIONS:This study shows that sex, age, comorbidities, and socioeconomic characteristics influence the prescription of systemic treatments in psoriasis, highlighting that there are still unmet needs influencing the therapeutic decision-making process that have to be addressed.